I—Testimony, Illocution and the Second Person. Issue 1 (4th June 2013) - Moran, Richard
<x xml:space="preserve">Abstract</x> The notion of 'bipolar' or 'second‐personal' normativity is often illustrated by such situations as that of one person addressing a complaint to another, or asserting some right, or claiming some authority. This paper argues that the presence of speech acts of various kinds in the development of the idea of the 'second‐personal' is not accidental. Through development of a notion of 'illocutionary authority' I seek to show a role for the 'second‐personal' in ordinary testimony, despite Darwall's argument that the notion of the 'second‐personal' marks a divide between practical and theoretical reason.